Retirement planning: are Selangorians ready? / Husin N. A., Munir A. N. and Rajain M. E. - Husin, N. A.; Munir, A. N.; Rajain, M. E. (2019)
Retirement planning is crucial for everyone to ensure that they are debt-free and financially secure when they have already stopped working. Retirement comes with a somewhat uncertain monetary stability as the ordinary income has decreased or ceased. The objectives of this research were to identify the related variables that influence retirement planning among working people in Selangor. A quantitative approach and purposive sampling of respondents were employed with the distribution of 120 sets of questionnaire to working people. The data was analysed using Smart-PLS 3.0. The results showed that out of the three identified independent variables, knowledge is the only predictor that had a statistically significant relationship with retirement planning; the path coefficient was .348 (p=0.00). Somehow, decision behaviour and retirement age had not significantly contributed to the variance in retirement planning. The effect size was evaluated, and it showed that knowledge had the most substantial influence on the retirement planning (f2=.068). A stimulating discussion has been reported to explain such finding. This finding is insightful for the employers of Selangor’s civil servants, as well as to the employers of private sectors, to safeguard the well-being of their greatest assets in managing their organisations effectively.